The effectiveness of video-assisted asynchronous learning on students' learning outcomes in the subject of akidah akhlak - Jamil, Alvian Nur; Thohir, Muhammad (Universitas Negeri Yogyakarta, 2023)
The role of technology in the education sector is increasing and has impacted the realm of learning activities. Technology-integrated learning is highly needed to facilitate both teachers and students in their activities. Using asynchronous learning models provides flexibility with easy and efficient access in terms of time. The research aims to describe the implementation of the asynchronous learning model assisted by videos in the subject of akidah akhlak, as well as the learning outcomes of the experimental and control groups, and the effectiveness of the asynchronous learning model assisted by videos in improving student learning outcomes. The research method used is quantitative with a proper experimental design. The experiment takes the form of a pretest-posttest control group design, with an experimental class receiving treatment in the form of asynchronous learning assisted by videos, and a control class implementing conventional methods. The research results show that the questionnaire on video implementation obtained a TCR score of 82.95% for variable X and 81.79% for variable Y, both falling within the 81-100% interval scale, indicating a